Research Review of women’s issues of ghusl in the light of the Narrations of the wives of the Rasool (PBUH): ازواج مطہرات کی مرویات کی روشنی میں خواتین کے مسائل غسل کا تحقیقی جائزہ - Naz, Hina; Bano, Dr. Najma (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Purity is called ‘Tahart’ in Arabic Tahart is not only cleanliness but also the purity of body, soul, clothes and environment. Islam gives guiding principles of life and purity and cleanliness have such a great importance in these principles that it seems as if the religion of Islam is based on them. In Islam particular emphasis is placed on ghusl to achieve purity. Ghusl of Janabah, menstruation, nifas and istihaza are directly related to men and women. The wives of the Rasool (PBUH) have played unparalleled role in this regard. By putting aside the “shari” shame and modesty, they have shad light on the different types and methods of ghusl. Modern issues related to ghusl such as artificial hair, dentures, nail polish, earring, nosering and prostheses are also mentioned in this article. So that people now a days take care of these things during ghusl and attain complete purity. Because of the imitation of modernism in the modern era, man is moving away from the basic Islamic teachings and is becoming a victim of various physical, mental and psychological confusions. There is a need to spread Islamic teachings about purity and holiness. This article will be useful for the young generation. So that they have awareness and consciousness in this regard.